ERP and oscillatory differences in overweight/obese and normal-weight adolescents in response to food stimuli - Stefanie C. Biehl; Julian Keil; Eva Naumann; Jennifer Svaldi (Journal of Eating Disorders, 2020)
Abstract Background Findings are mixed regarding the association of electroencephalographic (EEG) attentional bias measures and body weight, with few studies measuring food craving or intake and no study reporting oscillatory measures. Methods EEG data were collected while 28 satiated adolescents (14 overweight/obese) viewed pictures of neutral, low-calorie food, and high-calorie food stimuli and rated their desire to eat, before having access to high-calorie snacks. Results Unlike normal-weight adolescents, overweight/obese participants showed similar P300 amplitudes for high- and low-calorie food, and strongest event-related alpha band desynchronization for low-calorie stimuli. P300 amplitudes and state craving for low-calorie food furthermore predicted snack intake in this group. Conclusions The current research focus in overweight/obesity might need to be extended to include low-calorie food. While all participants showed an attentional bias for high-calorie food, it was the processing of low-calorie food which distinguished the two weight groups on measures of neural activity and which was associated with snack food intake in the overweight/obese group.